Melting and freezing under Antarctic ice shelves from a combination of ice- sheet modelling and observations - Bernales, Jorge; Rogozhina, Irina; Thomas, Maik (Freie Universität Berlin, 2017)
Ice-shelf basal melting is the largest contributor to the negative mass balance of the Antarctic ice sheet. However, current implementations of ice/ocean interactions in ice-sheet models disagree with the distribution of sub-shelf melt and freezing rates revealed by recent observational studies. Here we present a novel combination of a continental-scale ice flow model and a calibration technique to derive the spatial distribution of basal melting and freezing rates for the whole Antarctic ice-shelf system. The modelled ice- sheet equilibrium state is evaluated against topographic and velocity observations. Our high-resolution (10-km spacing) simulation predicts an equilibrium ice-shelf basal mass balance of −1648.7 Gt a−1 that increases to −1917.0 Gt a−1 when the observed ice-shelf thinning rates are taken into account. Our estimates reproduce the complexity of the basal mass balance of Antarctic ice shelves, providing a reference for parameterisations of sub- shelf ocean/ice interactions in continental ice-sheet models. We perform a sensitivity analysis to assess the effects of variations in the model set-up, showing that the retrieved estimates of basal melting and freezing rates are largely insensitive to changes in the internal model parameters, but respond strongly to a reduction of model resolution and the uncertainty in the input datasets.